Effect of smoking cessation programs on periodontal disease progression - Arti Dixit; P Dhanalakshmi; Pallavi Tripathi Rameshchandra; Karina S Chachlani; C Dithi; Kailash Chandra Dash; Vishnu Teja Obulareddy; Praveen Kumar Gonuguntla Kamma (Wolters Kluwer Medknow Publications, 2024)
Background: In this research study, we delve into the effects of smoking cessation programs on the progression of periodontal disease, particularly focusing on the potential benefits experienced by individuals who successfully quit smoking. Materials And Methods: The research involved the participation of 200 individuals, all of whom were active smokers and exhibited varying degrees of periodontal disease. These participants enrolled in a comprehensive smoking cessation program that included regular counseling sessions and, when necessary, the provision of nicotine replacement therapy to facilitate smoking cessation. Over a 12-month period, the progression of their periodontal disease was systematically monitored through a series of dental check-ups and measurements of critical clinical parameters. These parameters included probing depth (PD), which assesses the spaces between teeth and gums, and clinical attachment level (CAL), which evaluates the attachment of gum tissue to tooth surfaces. Results: After 12 months of active participation in the smoking cessation program, several noteworthy results were observed among the participants. On average, participants experienced a reduction in PD by approximately 1.5 mm, indicating a shallower space between the teeth and gums and, thus, healthier periodontal tissues. In addition, the CAL improved by an average of 1.2 mm, signifying enhanced attachment of gum tissue to the tooth surface, which is essential for dental stability. Participants also exhibited a significant reduction in plaque accumulation on tooth surfaces, indicative of improved oral hygiene practices. Furthermore, gingival inflammation, a common symptom of periodontal disease, notably decreased among participants, suggesting an overall improvement in gum health. Conclusion: In conclusion, this study provides compelling evidence supporting the positive impact of smoking cessation programs on the progression of periodontal disease.